tert-Butyl hydroperoxide, an organic peroxide, causes temporary delay in hair growth in a neonatal rat model - Wikramanayake, T. C. (2011)
tert-Butyl hydroperoxide (tBHP), an organic peroxide, has been shown to cause irreversible damage to keratinocytes in vitro with prolonged administration at high concentrations, and reversible damage with short-term administration at low concentrations. To investigate the effects of tBHP on keratinocytes in vivo, we analysed hair growth in tBHP-treated neonatal rats. Sprague–Dawley and Long–Evans rat pups were injected subcutaneously with tBHP or vehicle once daily for 6 days, and hair growth was monitored. The tBHP-treated rats had a significant delay in hair growth. However, this delay reversed within days, and the hair coats, including hair pigmentation, of tBHP-treated and sham-treated rats were indistinguishable 2 weeks later. Histological analysis and BrdU labelling of S phase cells confirmed the delay in hair-follicle growth and its reversal in tBHP-treated rats. Our results indicated that the changes incurred in hair follicles by short-term use of high-dose oxidants in vivo are temporary and reversible.